A new complexity reduction methods of V-BLAST MIMO system in a communication channel - Sunita Panda; Rosalin Samantaray; Pradyumna Ku. Mohapatra; R.N. Panda; Padma Sahu (Institute of Advanced Engineering and Science, 2019)
To design most reliable wireless communication system we need an efficient method which can be proposed in this paper is V-BLAST technique which is most powerful tool in MIMO system. To improve the channel capacity and data rate efficiently we need manifold antennas together with the transmitter and receiver. In this paper we have analyzed different equalizers performance using V-BLAST algorithm. We have proposed two methods i.e. low complexity QR algorithm and another is consecutive iterations reduction method. This methods compare with traditional finding methods such as ZF, MMSE, SIC and ML. The proposed algorithm shows that it not only reduce the computational complexity but we can achieve significant bit error rate (BER) and probability error compared to traditional VBLAST techniques.